Strategi manajemen risiko perbankan syariah: Adaptasi di era digital dan ketidakpastian ekonomi - ahady, ahmad auly (Maliki Interdisciplinary Journal, 2025)
Digital transformation and global economic uncertainty have created new challenges in banking risk management practices, including for Islamic banks that operate based on Sharia principles. This study aims to analyze the risk management strategies adopted by Islamic banks in responding to the dynamics of digitalization and economic volatility. Using a qualitative approach through literature review and case study analysis of several Islamic banks in Indonesia and Malaysia, the study identifies key types of risks, including technology-based operational risk, Sharia compliance risk, as well as reputational and liquidity risks. The findings indicate that Islamic banks have begun to integrate digital technologies such as artificial intelligence, data analytics, and system-based Sharia audits to strengthen risk mitigation. However, this adaptation still faces challenges in terms of information security, responsive Sharia supervision, and human resource capacity. The study concludes that risk management strategies in Islamic banking during the digital era must be holistic, collaborative, and value-based to maintain the sustainability and integrity of the Islamic financial system amidst a rapidly changing and uncertain environment.